A low complexity smoothing algorithm for improved GPS point solutions on board LEO spacecraft. Issue 1 (2nd February 2021) - Van Buren, Damon; Axelrad, Penina; Palo, Scott
Abstract: This paper describes a novel approach for reducing the kinematic position and time errors on a GPS receiver in low Earth orbit. For dual‐frequency GPS receivers, point solution errors are dominated by signal‐in‐space ranging errors, which introduce sharp discontinuities in the position and time estimates when GPS visibility changes. These discontinuities may be calculated and removed, greatly reducing the peaks of the errors, at the expense of introducing a slowly varying bias, which is estimated and removed. The paper gives a detailed description of the algorithm and illustrates its use on a GPS receiver using historical ephemerides. To demonstrate real‐world efficacy, GRACE‐FO observations are processed using the proposed approach. Real‐time results show the reduction of the time error standard deviation by 16% to 1.9ns and the reduction of the 3D RMS error by 17% to 1.06m. Maximum real‐time errors are reduced 26% and 32%, respectively. Delayed processing offers greater reductions of errors, near 40%.